(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The relative position of 30 main bioevents pertaining to calcareous nannofossils and planktonic foraminifera was identified in the time interval between 13.75 Ma and 10.50 Ma, based on the quantitative study of the those microfossils in three Mediterranean sections spanning the late Langhian – lower Tortonian stratigraphic interval. The events were correlated to the astronomic target curve using a cyclostratigraphic approach, resulting in a very detailed biostratigraphic and biochronologic subdivision of the interval. The zonal scheme proposed by Fornaciari et al. (1996) was adopted for the calcareous nannofossils, but three subzones were identified in the MMN7 Zone. For the planktonic foraminifera reference is made to the zonal scheme recently proposed by Foresi et al. (1998), slightly modified in order to increase its biostratigraphic resolution. The age of all the zonal boundaries is reported.